PEMBELAJARAN IPS DI SMP NEGERI 1 JELAI KABUPATEN SUKAMARA - Ifan Julianta (Universitas Lambung Mangkurat, 2014)
Determining factor in the learning is the role of a teacher. The main problem that became focus in this study described the role of social studies teacher at SMP Negeri 1 Jelai, such as: Demonstrator, Mediator and Facilitator, Class Administrator, and Evaluator. The research method used is descriptive qualitative. Data collection was performed by using in-depth interviews, participatory observation and documentation. The result found that (1) the learning social science was by using 2013 Curriculum for class VII and VIII, and KTSP Curriculum for grade IX. Nevertheless, in the implementation of the process there were some constraints in terms of books and other supporting facilities such as the incomplete media, as well as the factors from students themselves; (2) The teacher has done his role as a demonstrator. however, this role was not optimally performed since he was still using conventional method; (3) the roles of the teacher as mediator and facilitator have been well implemented yet not fully applied since he was still only used text books; (4) the role of the teacher as a class administrator has been well performed; (5) the role of the teacher as an evaluator has been well performed. Keywords: Learning, Social Studies, and Role Teacher